Pemanfaatan Akun Instagram @lib.unand dalam Pemenuhan Kebutuhan Informasi Mahasiswa Universitas Andalas - Cantika, Vanesya; Nabila, Jeihan (Scinary, 2025)
This study discusses the utilization of the Instagram account @lib.unand by the Universitas AndalasLibrary in fulfilling students' information needs. Using a descriptive quantitative approach, datawere collected through questionnaires distributed to 381 students selected using Slovin's formulafrom a total of 8,060 followers. The research instrument was based on the Uses and Gratificationtheory, which includes cognitive, affective, personal, social, and escapist needs. The results showthat the account generally supports students' information needs with an average score of 3.21.Cognitive needs scored the highest (3.34), followed by personal (3.29), social (3.20), affective(3.17), and escapist (3.06). These findings indicate that students mainly use the account to obtainacademic information and strengthen personal identity. This study recommends enhancing contentvariety and user interaction to optimize the effectiveness of digital library services. Keywords: Instagram, information needs, academic library, student engagement, social media